Pengelolaan Pajak Daerah dalam Prespektif Manajemen Islam - Gus Nur Wahid , Muhammad; Mustofa , Lutfi; Handoko , Cipto (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
Tax is one of the largest sources of state revenue. Local tax management policies are still not running optimally due to the lack of awareness from the public about the importance of taxes and the lack of strict sanctions given by the government to the community and the lack of organizational commitment. Tax management according to Islamic management The state is obliged to fulfill the following conditions: Receipt of tax proceeds must be seen as a trust and spent honestly and efficiently and distribute the tax burden evenly, and emphasize that a fair taxation system is in line with the spirit of Islam. Reasons for paying taxes. guarantee of solidarity. rules based on the Qur'an and Sunnah. and this principle of justice must be adhered to, both in principles regarding legislation and in practice. By its nature tax is an additional obligation (tathawwu'), for Muslims after Zakat, in Islam which is one of the state revenues based on Ulil Amri ijtihad approved by the House of Representatives (Ahlil halli wal aqdi) and the approval of Ulama